2020
DOI: 10.1021/acs.macromol.0c01906
|View full text |Cite
|
Sign up to set email alerts
|

Percolated Ionic Aggregate Morphologies and Decoupled Ion Transport in Precise Sulfonated Polymers Synthesized by Ring-Opening Metathesis Polymerization

Abstract: We describe a set of precise single-ion conducting polymers that form self-assembled percolated ionic aggregates in glassy polymer matrices and have decoupled transport of metal cations. These precise single-ion conductors (SICs), synthesized by a scalable ring-opening metathesis polymerization, consist of a polyethylene backbone with a sulfonated phenyl group pendant on every fifth carbon and are fully neutralized by a counterion X+ (Li+, Na+, or Cs+). Experimental X-ray scattering measurements and fully atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 86 publications
0
54
0
Order By: Relevance
“…Temperature modulated differential scanning calorimetry (DSC) indicates a T g of 103 °C when dry. 17 The detailed synthesis and further characterization of the purity of these materials, including thermal gravimetric analysis, size exclusion chromatography, nuclear magnetic resonance (NMR) spectroscopy, and DSC, were reported previously. 13 Samples were prepared from 2 to 3 weight % of lyophilized p5PhSA polymer dissolved in deionized water.…”
Section: Synthesis and Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature modulated differential scanning calorimetry (DSC) indicates a T g of 103 °C when dry. 17 The detailed synthesis and further characterization of the purity of these materials, including thermal gravimetric analysis, size exclusion chromatography, nuclear magnetic resonance (NMR) spectroscopy, and DSC, were reported previously. 13 Samples were prepared from 2 to 3 weight % of lyophilized p5PhSA polymer dissolved in deionized water.…”
Section: Synthesis and Sample Preparationmentioning
confidence: 99%
“…[13][14][15][16] We recently investigated p5PhSA neutralized with a variety of metal cations, and found that in the dry state the ions and sulfonate groups strongly nanophase separate from the polymer backbone and self-assemble into percolated ionic aggregates. 17 We thus anticipated that p5PhSA would also nanophase separate into hydrophilic and hydrophobic domains. Accessing high proton conductivity with this polymer could lead to a new class of scalable materials for use as PEMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the bulk state, p 5PhS‐Li has been recently shown to nanophase separate into percolated ionic networks driven by the flexible yet non‐polar nature of the PE backbone/phenyl rings versus the precisely spaced polar regions of the neutralized sulfonate species. [ 39 ] These networks are persistent over a large temperature range. Combining this nanophase self‐assembly with another component (PEO) may be resulting in complex phase behavior of these blends at the varying compositions studied.…”
Section: Discussionmentioning
confidence: 99%
“…[ 49,50 ] Nonetheless, the experimental results indicate some degree of miscibility, which must be the case for the blends to exhibit higher ionic conductivity than that of neat p 5PhS‐Li due to the dissociation of lithium ions into PEO. Neat p 5PhS‐Li exhibits at least 2 orders lower ionic conductivity [ 39 ] at the same measured temperature as p 5PhS‐Li/PEO blends at all compositions.…”
Section: Discussionmentioning
confidence: 99%